Students’ vulnerability to cybercrime: implications for cybersecurity in the global south - Abah, Joshua Abah; Agada, Peter Inalegwu (International Journal of Didactic Mathematics in Distance Education, 2025)
This conceptual study examines key issues around students’ vulnerability to cybercrimes in the Global South. The increasing digitalization of education has exposed students in the Global South to heightened risks of cybercrime. Limited cybersecurity awareness, inadequate digital infrastructure, and socio-economic vulnerabilities make students particularly susceptible to cyber threats such as phishing, identity theft, and online fraud. This article examines the key factors contributing to students’ exposure to cybercrime, including gaps in digital literacy, institutional cybersecurity policies, and the role of social and economic disparities. It also explores the broader implications for cybersecurity frameworks in the Global South, emphasizing the need for enhanced policy interventions, education reforms, and multi-stakeholder collaborations. By addressing these challenges, governments, educational institutions, and technology providers can foster a safer digital environment for students, ultimately strengthening overall cybersecurity resilience in the region. The study underscores the need for targeted cybersecurity awareness programmers and institutional policies to enhance students’ online safety.